Representasi Tindakan Sosial Dalam Lirik Lagu Album "Untuk Dunia, Cinta, Dan Kotornya" Karya Nadin Amizah: Perspektif Max Weber - Kharisma Alya Firmanda; Yuniseffendri Yuniseffendri (Jurnal Ilmu Bahasa, Sastra, dan Budaya, 2026)
Song lyrics are contemporary literary works that are interesting to study because they not only serve as entertainment but also become a medium for representing social or personal issues. This study aims to describe the representation of social actions in the lyrics of the album "Untuk Dunia, Cinta, dan Kotornya" by Nadin Amizah. This type of research is qualitative with a literary sociology approach. The research data sources consist of eleven songs from the album, with research data in the form of lyric excerpts analyzed through observation, reading, and noting techniques. Data analysis in this study was carried out through stages of reduction, classification, interpretation, data presentation, and conclusion drawing. The conclusions indicate that (1) recovery, preparation, and cultivation actions are forms of representation of instrumental rational actions, and (2) recognition, affection, and acceptance actions are forms of representation of value-oriented rational actions, (3) feelings of disgust and relief are a form of affective action representation, and (4) doctrinal and habitual actions are a form of traditional action representation. Thus, this study shows that songs are not only used as a form of entertainment, but can also serve as a medium to represent various social and personal issues.